Seasonal changes in biochemical composition of the clam Eurhomalea exalbida (Bivalvia,Veneridae) from Ushuaia Bay (54º 50'S), Beagle Channel (Argentina) - Lomovasky, Betina Judith (2004)
Seasonal changes in biochemical composition (protein, glycogen and lipid content) of different organs (FV: foot-visceral mass, M: adductor muscles and GMS: gills-mantle-siphons) of the clam Eurhomalea exalbida from Ushuaia Bay (54º 50´ S, Beagle Channel, Tierra del Fuego) were examined to describe changes in relation to reproduction and growth. A maximum level of protein content was observed during winter in all tissues, with other increase during the spawning event (November) in FV and in November and January in GMS. In the adductor muscle, the protein content shows low variability during the year, except in June. Suggesting that all these tissues are involved in the storage of proteins, which are thought to play a role in vitellogenesis. The percentage of glycogen content for FV, M and GMS showed low values (0.03% to 4.7% AFDW) along the year, which suggest that these components did not have an important function as substrate for energy reserves. Low values of lipid content for FV were found in November with increased levels in summer season. Thus, the lipid content variations can be related principally to gamete emission in November and the vitellogenesis in summer season. The high levels of lipid content in FV over the rest of the year were correlated with the presence of mature gonads throughout the major part of the year. Therefore, our results suggest that in E. exalbida: (a) proteins are the most important storage substrate; (b) the relative content of protein, lipid and glycogen of the adult specimens vary seasonally in accordance with the reproductive cycle and the season of maximum growth, when the organism reaches reproductive maturity (summer), shell growth slows down because of reproductive investment.